Effects of open drainage ditch design on bacterial and fungal communities of cold waterlogged paddy soils - Qiu,Shanlian (2013)
A field experiment established in 1980 was conducted to evaluate the effects of open drainage ditch applied for water removal on bacterial and fungal communities of cold waterlogged paddy soils in 2011. In this experiment, traditional plate counting and temperature gradient gel electrophoresis were employed to characterize the abundance and diversity of soil bacterial and fungal communities. Four different distances from the open drainage ditch, 5, 15, 25 and 75 m with different degrees of drainage were designed for this study. Maximum populations of culturable aerobic bacteria and fungi were at 15-m distance while minimum populations were at 75-m distance. Significant differences (p < 0.05) in fungal populations were observed at all distances from open drainage ditch. The highest diversity of the bacterial community was found at a distance of 25 m, while that of the fungal community was observed at a distance of 5 m. Sequencing of excised TGGE bands indicated that the dominant bacteria at 75-m distance belonged to anaerobic or microaerobic bacteria. Relationships between microbial characteristics and soil physicochemical properties indicated that soil pH and available nitrogen contents were key factors controlling the abundance of culturable aerobic bacteria and fungi, while soil water capacity also affected the diversity of fungal community. These findings can provide the references for better design and advanced management of the drainage ditches in cold waterlogged paddy soils.